Humoral and Cell-Mediated Immune Response Validation in Calves after a Live Attenuated Vaccine of Babesia bigemina - Umber Rauf (Pathogens, 2020)
The current vaccines to control bovine Babesia bigemina (B. bigemina) infection are not fully protective and vaccination failures incur heavy losses to the cattle industry around the world. Using modified micro-aerophilous stationary phase, we developed a culture-derived attenuated live vaccine against B. bigemina and tested a single subcutaneous inoculation of 2 × 108 infected erythrocytes in calves. The protection was measured after a lethal intravenous challenge with 5 × 108 virulent calf-derived B. bigemina. Our results demonstrated that a single shot of attenuated vaccine was capable of inducing robust humoral and cell-mediated immune responses in calves. We found a significant increase in the IgG antibody titers post-challenge and a strong proliferation of both CD4+ and CD8+ T cells contributing towards the protection. Our vaccine provided complete protection and parasitic clearance, which was followed for more than 100 days post-challenge. This immunity against babesiosis was directly linked to strong humoral responses; however, the parasitic clearance was attributed to significant T cells effector responses in vaccinated calves as compared to the infected control calves. We anticipate that these results will be helpful in the development of more efficient culture-derived vaccines against Babesia infections, thus reducing significant global economic losses to farmers and the cattle industry.